Overview of Depression - Tri Mayasari, Ni Nyoman Wistya (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Depression is a state of disorder tone generally feeling characterized by feelings of sadness, apathy, pessimism, and loneliness. Epidemiology of depression showed a lifetime prevalence of 7-12% for men and 20-25% for women. The reason for the prevalence differences between men and women not much can be explained, but biological factors and socio-cultural influences. In the depression is sadness lasts for days so that it can disrupt work, study, eat, sleep, and enjoyment. The cause of depression is not just one, but multifactorial. Most of the cause may arise from or the people themselves. Because it is not clear on anatomy, biochemistry, or physiology. To diagnose depression may use criteria of PPDGJ or using DSM-IV-TR /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: depression, sad